2011
DOI: 10.1021/cn200016q
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adenosine Receptors by [60]Fullerene Hydrosoluble Derivative in SK-N-MC Cells

Abstract: The most known fullerenes are spherical carbon compounds composed of 60 carbon atoms. C60 fullerenes have shown biochemical and biomedical properties in the last years such as as blockade of apoptosis and neuroprotection. The nucleoside adenosine has a neuroprotective role mainly due to inhibition of glutamate release, which is a neurotransmitter related to excitotoxicity and cell death. In the present work, we have determined the presence of adenosine receptors in SK-N-MC cells, a neuroepithelioma human cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
3
3
0
3
Order By: Relevance
“…In line with this, the observed increase in A 1 ARs gene expression by t3ss derivative, as it has been previously reported in SK-N-MC cells [23], could be related to the described protective role exerted by these receptors during hypoxic conditions [30]. …”
Section: Resultssupporting
confidence: 82%
“…In line with this, the observed increase in A 1 ARs gene expression by t3ss derivative, as it has been previously reported in SK-N-MC cells [23], could be related to the described protective role exerted by these receptors during hypoxic conditions [30]. …”
Section: Resultssupporting
confidence: 82%
“…Tetracationic fullerene C60 derivative VII. 271 Specific interaction between fullerene and proteins at the molecular level was mentioned above (see, e.g., Ref. 278).…”
Section: Iii3 Biomedical Applicationsmentioning
confidence: 87%
“…15). 191,271 One of the most striking proofs of the ability of fullerenes to interact with proteins is the formation of fullerene-specific antibodies obtained for the water-soluble C 60 and C 70 fullerene derivatives. 272 An X-ray study of a Fab fragment of an antibody showed that the fullerene-binding site contains amino acids of both chains.…”
Section: Iii3 Biomedical Applicationsmentioning
confidence: 99%
“…Так, показано, что концентрация аденозин-А1-и А2А-рецепторов в клетках SK-N-MC увеличивалась после обработки производными фул-лерена, при этом существенно не влияя на жизне-способность клеток [47].…”
Section: фуллерен и биологические молекулыunclassified